Physical injury and psychotic experiences in 48 low- and middle-income countries. Issue 16 (22nd December 2020) - Stickley, A.; Sumiyoshi, T.; Narita, Z.; Oh, H.; DeVylder, J. E.; Jacob, L.; Koyanagi, A.
Abstract: Background: Psychotic experiences (PEs) may be associated with injuries, but studies focusing specifically on low- and middle-income countries (LAMICs) are scarce. Thus, the current study examined the link between injuries and PEs in a large number of LAMICs. Method: Cross-sectional data were used from 242 952 individuals in 48 LAMICs that were collected during the World Health Survey in 2002–2004 to examine the association between traffic-related and other (non-traffic-related) forms of injury and PEs. Multivariable logistic regression analysis and meta-analysis were used to examine associations while controlling for a variety of covariates including depression. Results: In fully adjusted analyses, any injury [odds ratio (OR) 2.07, 95% confidence interval (CI) 1.85–2.31], traffic injury (OR 1.84, 95% CI 1.53–2.21) and other injury (OR 2.09, 95% CI 1.84–2.37) were associated with higher odds for PEs. Results from a country-wise analysis showed that any injury was associated with significantly increased odds for PEs in 39 countries with the overall pooled OR estimated by meta-analysis being 2.46 (95% CI 2.22–2.74) with a moderate level of between-country heterogeneity ( I 2 = 56.3%). Similar results were observed across all country income levels (low, lower-middle and upper-middle). Conclusions: Different types of injury are associated with PEs in LAMICs. Improving mental health systems and trauma capacity in LAMICs may be important for preventing injury-related negative mental health outcomes.